ИСПОЛЬЗОВАНИЕ ОБЛАЧНЫХ ТЕХНОЛОГИЙ В УПРАВЛЕНИИ СРЕДНЕЙ ОБЩЕОБРАЗОВАТЕЛЬНОЙ ШКОЛЫ - Закирова, М.Р. (SCIENCE and SOCIETY, 2023)
In recent years, there has been a trend in the field of information technology to use "clouds". Cloud technologies have now entered many areas, in particular, education. Cloud computing provides users with better and more secure data management, calculation, storage and other services through unique resource sharing and convenient management and maintenance. Also, the use of cloud technologies in the formation of an innovative information and management environment of the school has created a new look at the management of an educational organization. The research is devoted to the actual problem of using cloud technologies in the management of a secondary school, caused by the demands of the digitalization of education.